Atrazine, mesosulfuron‐methyl, and topramezone persistence in North Carolina soils. (29th March 2022) - Ramanathan, Shwetha S.; Gannon, Travis W.; Everman, Wesley J.; Locke, Anna M.
Abstract: Investigating the effects of soil properties on herbicide persistence can aid in evaluating the carryover potential of herbicides in soil and the consequent injury risk to rotational crops. Laboratory incubation experiments were conducted to quantify the persistence of atrazine, mesosulfuron‐methyl, and topramezone in five regional soils under aerobic conditions at 23 °C. Additionally, mesosulfuron‐methyl persistence was tested at 7 °C, which is representative of regional average winter soil temperature. Herbicide half‐life was calculated with the logarithmic form of first‐order rate of degradation using linear regression and was correlated with soil properties. Half‐lives of atrazine (37–73 d) and topramezone (15–19 d) varied among soil types at 23 °C. Mesosulfuron‐methyl half‐life varied among soils at 7 °C (8.8–9.8 d) and 23 °C (5.4–5.8 d) and between temperatures. Atrazine and topramezone half‐lives were shortest in Candor sand (4% clay, 1.8% organic matter [OM], pH 5.1) and longest in Portsmouth sandy loam (13% clay, 5.3% OM, pH 4.3). Mesosulfuron‐methyl half‐life was longer at lower soil temperature. Half‐lives of atrazine, mesosulfuron‐methyl, and topramezone were correlated with soil OM content ( r  = .83, −.53, and .63, respectively) and pH ( r  = −.86, .55, and −.57). Additionally, atrazine and topramezone half‐lives were positively correlated with soil clay content ( r  = .83 and .71), and mesosulfuron‐methyl half‐life was negatively correlated with temperature ( r  = −.97). Correlations between soil OM content, clay content, and pH among soil types may have influenced herbicide persistence. Core Ideas: Half‐lives of atrazine and topramezone varied among soil types at 23 °C. Half‐life of mesosulfuron‐methyl varied among soils and between 7 and 23 °C. Herbicide half‐life was correlated with soil OM content, clay content, pH, and temperature. Correlations between soil OM content, clay content, and pH may influence herbicide persistence.